Pengaruh Media Sosial dalam Meningkatkan Brand Awareness Wizzmie di Era Digital - Salsabilah, Dea (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
In today's digital era, social media is one of the most effective tools to build brand awareness and reach the wider community. This study aims to analyze the influence of social media to support increasing brand awareness and Wizzmie customer growth. Wizzmie is a culinary business that focuses on making a variety of instant noodles. The method used is a quantitative approach by filling out questionnaires to active consumers of Wizzmie and analyzing social media such as Instagram and Tiktok. The results of the study show that the intensity and quality of content published through social media often have a positive impact on increasing brand awareness. In addition, direct interaction with consumers and creative digital interactions significantly contribute to increased buying interest and customer loyalty. These findings strengthen the strategic role of social media as the main means to build brand awareness in the midst of competition in the digital culinary industry.